2013
DOI: 10.1063/1.4824852
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent velocity profiles in a tilted heat pipe

Abstract: In this paper, we analyze the mean velocity profile and the Reynolds shear stress in a turbulent, inclined, heat pipe. We show that the simplest version of a mixing length model is unable to reproduce the evolution of the velocity profile shape with the inclination angle psi. An improvement of this model, taking into account some buoyancy effects, gives nice qualitative agreement with the observations. The agreement implies surprisingly a low value for the gradient Richardson number Ric above which the flow is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…An attempt based on the mixing length approximation was recently reported by Salort et al (2013) in the case of a prescribed axial density gradient. This model emphasizes the crucial role of the stabilizing stratification as Θ increases and introduces empirical corrections to the usual mixing length definition to cope with this influence.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt based on the mixing length approximation was recently reported by Salort et al (2013) in the case of a prescribed axial density gradient. This model emphasizes the crucial role of the stabilizing stratification as Θ increases and introduces empirical corrections to the usual mixing length definition to cope with this influence.…”
Section: Final Remarksmentioning
confidence: 99%
“…For Θ 20 • , the corresponding mean velocity and shear stress profiles are similar to those of Znaien et al (2009), and the smaller Θ the lower the critical Rayleigh number required to reach the 'hard' regime. New data by the same group in the range 5 • Θ 20 • (Salort et al 2013) were interpreted in the light of a mixing length model, but the observed Θ-dependence of the mean velocity profile could only be recovered by altering the usual time scale of Prandtl's original model (i.e. the inverse of the mean shear) with contributions resulting from both the stabilizing and destabilizing buoyancy components.…”
mentioning
confidence: 99%